Microbial profile and putative microbial origin of anorectal abscess based on 16S rDNA sequencing - Chen, Shanzhong; Dai, Chun; Zhao, Hongyuan; Gu, Yifan; Sun, Kuijun; Yao, Xingran; Jiang, Feng; Shi, Renjie (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAnorectal abscess is a common bacterial infectious disease; however, its pathogenesis remains unclear. Although there is emerging evidence linking gut microbiota to anorectal abscesses, knowledge of the microbial origin of this disease remains limited. This study analyzed the microbial profile of anorectal abscesses using 16S rDNA sequencing and investigated their microbial origin with the aim of providing a reference for subsequent studies.MethodsWe recruited 60 patients with anorectal abscesses (AA group) and 26 healthy individuals (HC group) and used 16S rDNA V3-V4 hypervariable region gene sequencing to analyze the microbiota in feces, pus, and perianal buttock skin samples. The gut microbiota and perianal buttock skin flora were compared between the two groups, pus flora was analyzed in relation to the gut and perianal buttock skin microbiota, and microbial traceability analysis of pus was performed.ResultsThere were significant differences in the gut microbiota between the AA and HC groups. Escherichia-Shigella and Prevotella were significantly more prevalent, and Bacteroides, Faecalibacterium, and Blautia were decreased at the genus level in the AA group. Escherichia-Shigella and Prevotella were the main differential bacteria in the AA group and could be considered signature microbes of anorectal abscess. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis also showed significant differences between the two groups, with the AA group showing the most enrichment for protein families: metabolism. No significant difference in the perianal buttock skin flora was found between the two groups. The gut microbiota of patients with anorectal abscesses is similar to the pus flora than perianal buttock skin flora; hence, the gut microbiota is the putative microbial origin of the pus flora.ConclusionOur study provides a microbiomic panorama and putative microbial origin of anorectal abscesses, potentially offering new insights into their etiology, prevention, and treatment.